2002
DOI: 10.1103/physrevb.65.144403
|View full text |Cite
|
Sign up to set email alerts
|

Orbital ordering inLaMnO3:Electron-electron and electron-lattice interactions

Abstract: The interactions between eg orbitals in neighboring sites are investigated in LaMnO3 by taking into account virtual exchange of electrons and phonons. The spin and orbital ordering temperatures and the spin wave dispersion relation are calculated. We find that the orbital ordering is mainly caused by the electronic interactions and that the Jahn-Teller coupling is much smaller than that reported previously. We propose that the elastic constant shows a characteristic change at the Néel temperature by the spin a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 48 publications
(110 reference statements)
3
43
0
Order By: Relevance
“…Indeed, these anisotropic interactions are known to be very important in a context of the orbital orders in LaMnO 3 . 40,41) …”
Section: Comparison To the Antiferro 3-state Potts Modelmentioning
confidence: 99%
“…Indeed, these anisotropic interactions are known to be very important in a context of the orbital orders in LaMnO 3 . 40,41) …”
Section: Comparison To the Antiferro 3-state Potts Modelmentioning
confidence: 99%
“…The crystal structure contains tilted and rotated MnO 6 octahedra along with cooperative JT instabilities characterized by two short (s = 1.903Å), two long (l = 2.184Å), and two medium (m = 1.957Å) Mn-O bond distances [27]. These distortions lift the degeneracy of the singly occupied e g orbital and stabilize the system into an orbital-ordered state [28,29]. Hole-doping or raising the temperature produce a pseudo-cubic structure with FM half-metallic character [24,30,31] and small volume decrease of 2-4%.…”
Section: Introductionmentioning
confidence: 99%
“…Different points of view have been reported regarding the relative importance of the inter-and intra-orbital Hubbard interactions and the JT interaction in the manganites [23,24]. Although the electron-electron (ee) interactions are large in these systems, it has been suggested that the parent insulator can not be considered as a canonical Mott insulator [25].…”
Section: Introductionmentioning
confidence: 99%